The role of HIF-lalpha and hypoxia in the preferential response of prostate tumours to microtubule-targeting agents - Forde, James Christopher (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2010)
Tumour hypoxia is emerging as a common feature of prostate tumours associated with poor prognosis mainly due to their resistance to chemo- radiotherapy regimes. The efficacy of microtubule-targeting agents (MTAs) has recently been shown to be modulated by Hypoxia-Inducible-Factor-1 alpha (HIF-1α). HIF- 1α over expression has been reported to occur in almost 70% of all human tumours including prostate cancer.
Keywords: Clinical Medicine, M.D.; M.D. Trinity College Dublin